2013
DOI: 10.1149/2.011311jss
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Noise Studies on Fully Depleted UTBOX Silicon-on-Insulator nMOSFETs: Challenges and Opportunities

Abstract: The low-frequency (LF) noise behavior of Fully Depleted (FD) Ultra-Thin Buried Oxide (UTBOX) Silicon-on-Insulator (SOI) nMOSFETs is described from the perspective of the three major noise sources: 1/f-like or flicker noise, associated with carrier trapping/detrapping in the gate oxide; Generation-Recombination (GR) noise due to processing-induced defects in the thin silicon film and single-oxide-trap-related Random Telegraph Noise (RTN). It is shown that the fully depleted nature of the thin silicon films (<20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…As CMOS technology dimensions reach the nanoscale, both static and dynamic variability affect the device and circuit performance . Dynamic variability, better known as low‐frequency (LF) noise, generally scales with the inverse of the transistor area, so that large current fluctuations with time can occur in small transistors . Ultimately, this results in so called random telegraph noise (RTN), caused by a single defect in the device.…”
Section: Introductionmentioning
confidence: 99%
“…As CMOS technology dimensions reach the nanoscale, both static and dynamic variability affect the device and circuit performance . Dynamic variability, better known as low‐frequency (LF) noise, generally scales with the inverse of the transistor area, so that large current fluctuations with time can occur in small transistors . Ultimately, this results in so called random telegraph noise (RTN), caused by a single defect in the device.…”
Section: Introductionmentioning
confidence: 99%
“…5). This has been clearly validated by the presence of RTSs in the same transistors, connected with these film-related defects [7]. It can be demonstrated that the carrier generation by a SRH center is very sensitive to the activation energy, whereby close-to-mid-gap levels are most efficient [5].…”
Section: Lf Noise and Retention In Utbox Soifbrammentioning
confidence: 63%
“…Note, however, that the noise PSD is spread over more than two decades, compared with one decade for the retention time. A detailed analysis of the latter parameter has shown that the dispersion in noise magnitude is due to the presence of excess Lorentzian noise, corresponding with OR centers in the silicon film [6,7]. This is illustrated in Fig.…”
Section: Lf Noise and Retention In Utbox Soifbrammentioning
confidence: 89%
See 1 more Smart Citation
“…The RTN origin in UTBOX devices, i.e., the silicon film, front gate oxide or buried oxide, can be identified by measuring the noise spectral density for different bias conditions. Analysis of the noise at one interface can give information on the trap origin, by imposing the accumulation mode at the other interface, thereby screening the influence of the corresponding oxide traps from the other interface [3], [4].…”
Section: Introductionmentioning
confidence: 99%